PENGARUH KONSENTRASI DAN WAKTU PEMBERIAN EKSTRAK DAUN BIDURI (Calotropis gigantea) DALAM MENEKAN PERKEMBANGAN KEONG MAS PADA TANAMAN PADI SAWAH - Mawar Mawar; Ayu Kartini Parawansa; Abdullah Abdullah (Percetakan Umi Toaha Makassar, 2022)
The aim of the study was to determine the concentration and timing of giving of biduri leaves extract which could suppress the development of golden snail pests on paddy rice plants in rice fields. The study used a randomized block design (RBD) and treatment with two factors, namely the concentration of Calotropis gigantea fresh extract 50 %, 60 %, 70 %, 80 % and the time of giving of biduri leaves extract in (the morning at 06.00 am, the daylight at 12.00 am, the afternoon at 16.00 pm, the evening at 19.00 pm). Each treatment unit was placed in a rice planting tank (50 cm x 50 cm) which contained 12 clumps of rice plants and was given 10 gold snails. The results showed that the concentration of biduri leaves extract had a significant effect on mortality and suppressed the development of golden snail pests. The best concentration of the fresh extract of Calotropis gigantean was 80% and was given at 19.00 the light attack intensity category was 29.30%. Giving a concentration of 70% fresh extract of Calotropis gigantean with a time of giving at 19.00 in the evening gave better results in suppressing the development of golden snails in rice plants. The use of biduri leaves extract was effective in exterminating golden snails and was environmentally friendly.